Application of Biochar Functionalized with Layered Double Hydroxides: Improved Plant Growth Performance after Use as Phosphate Adsorbent - Jittrera Buates; Tsuyoshi Imai (Applied Sciences, 2021)
The objective of this study was to verify the feasibility of using biochar, functionalized with layered double hydroxides, as a fertilizer after its use in phosphate treatment (P-BC-LDHs). It was conducted with several levels of P-BC-LDHs using seed germination and early growth assays of lettuce (Lactuca sativa L.). The application of P-BC-LDHs resulted in successful seedling emergence, with an excellent germination capacity of over 96% for all treatments. However, compared to the controls, P-BC-LDHs did not provide favorable seedling traits. In contrast, in the latter experiments, lettuce cultivated under mixtures with P-BC-LDHs, particularly at an application rate of 2.5% (w/w), displayed superior growth quality to those under non-treated conditions. The length of lettuce shoots and roots from this optimal dosage were increased by at least 24% compared to untreated samples. A 17% reduction in biomass yield was observed for the samples from non-supplemented substrates. The nutrient release profiles showed that P-BC-LDHs were capable of slowly supplying phosphorus, thereby increasing the long-term nutrient availability for plants. The findings reported here provide important insights into these materials and confirm that P-BC-LDHs can be used for agricultural purposes after phosphate remediation applications. The results of this study provide constructive information to facilitate the implementation of biochar-based LDH composites for sustainable phosphate removal and recovery.